Infeksi Cacing Nematoda Pada Usus Halus Babi di Lembah Baliem dan Pegunungan Arfak Papua - Guna, I Nyoman Wijaya; Suratma, Nyoman Adi; Damriyasa, I Made (Buletin Veteriner Udayana, 2014)
The purpose of this study was to identify the nematode of the small intestine of pigs in Arfak Mountains and Baliem Valley in Papua, and determine the prevalence of the nematode infection. Small intestine content of 20 pigs originated from Arfak Mountains and 10 pigs from Baliem Valley were examined to identify the nematode species. Four species of nematodes were found in small intestine of pigs namely, Strongyloides ransomi, Ascaris suum, Macracanthorhyncus hirudinaceus, and Globocephalus urosubulatus . The result of the study showed that the prevalence of nematode infections in small intestine  were highly, in which the Baliem Valley had the prevalence of 90%, and 40% in Arfak Mountains.
Keywords: nematode, swine small intestine, Papua